2021
DOI: 10.1002/hep.32149
|View full text |Cite|
|
Sign up to set email alerts
|

Mitochondrial bioenergetics boost macrophage activation, promoting liver regeneration in metabolically compromised animals

Abstract: Background and Aims: Hepatic ischemia-reperfusion injury (IRI) is the leading cause of early posttransplantation organ failure as mitochondrial respiration and ATP production are affected. A shortage of donors has extended liver donor criteria, including aged or steatotic livers, which are more susceptible to IRI. Given the lack of an effective treatment and the extensive transplantation waitlist, we aimed at characterizing the effects of an accelerated mitochondrial activity by silencing methylation-controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 48 publications
0
33
1
Order By: Relevance
“…10,11 Of them, KCs exert significant functions in liver homeostasis, 12 hepatocellular carcinoma, 13 and liver regeneration. 14 It has been reported that F4/80 + KCs promote the proliferation of hepatocytes via releasing oncostatin, 15 while systemic depletion of KCs significantly retards the progress of liver regeneration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Of them, KCs exert significant functions in liver homeostasis, 12 hepatocellular carcinoma, 13 and liver regeneration. 14 It has been reported that F4/80 + KCs promote the proliferation of hepatocytes via releasing oncostatin, 15 while systemic depletion of KCs significantly retards the progress of liver regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, non‐parenchymal cells, such as Kupffer cells (KCs), natural killer cells (NKs), and sinusoidal endothelial cells, are involved in this process 10,11 . Of them, KCs exert significant functions in liver homeostasis, 12 hepatocellular carcinoma, 13 and liver regeneration 14 . It has been reported that F4/80 + KCs promote the proliferation of hepatocytes via releasing oncostatin, 15 while systemic depletion of KCs significantly retards the progress of liver regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…AML12 was grown in DMEM:F12 (Thermo Fisher # 11320033) medium supplemented as instructed by supplier; HuH-7 were grown in DMEM (Thermo Fisher #12100061) and Hep-G2 in DMEM supplemented with 2 mM glutamine and 2 mM pyruvate. Primary hepatocytes were isolated from livers of 2–3-month-old wild mice by two-step collagenase perfusion method [ 34 ], seeded at 65000 cells/cm 2 in collagen-coated glass coverslips in 24-well plates and maintained in MEM supplemented with 10% FBS, 2 mM glutamine and antibiotics at 37 °C and 5% CO 2 overnight until use.…”
Section: Methodsmentioning
confidence: 99%
“…Autophagy may be impaired during the pathogenesis of ischemic reperfusion injury (IRI), resulting in poor tolerance to IRI [ 24 ]. Strategies that reduce ROS production and liver damage, and improve mitochondrial functionality and ATP secretion could help to expand the available pool for transplantation [ 25 ].…”
Section: Introductionmentioning
confidence: 99%